Faktor Procrastination Penyebab Mahasiswa Terlambat Menyelesaikan Tugas Akhir di Program Studi Pendidikan Matematika - Daniel Jeremy; Stevi Natalia; Jitu Halomoan Lumbantoruan (Brillo Journal, 2021)
This study uses a form of analysis with a qualitative descriptive technique. This study involved final year students who were late in completing their thesis. This research was conducted online due to the COVID-19 outbreak. In this study, researchers used accidental sampling technique. Accidental sampling is a sampling technique based on chance. Methods of data collection using the questionnaire method. The results showed that students in working on the thesis encountered many obstacles in internal factors, namely self-control, self-efficacy, and motivation.